2016
DOI: 10.1007/s00011-016-0952-z
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of Wip1 involves in neuroinflammation of retinal astrocytes after optic nerve crush via NF-κB signaling pathway

Abstract: These data were consistent with the hypothesis that Wip1 was implicated in neuroinflammation of retinal astrocytes after ONC via NF-κB signaling pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…The elevation of these cytokine can be linked to the ability of Wip1 to regulate p53 and NF k B pathways. 40,41 These data suggest that Wip1 in immune cells intrinsically controls the sensitivity to DSS-induced colitis through regulation of cytokine production. Yet, the deficiency in Wip1 activity is associated with more severe inflammatory response.…”
Section: Wip1 In Regulation Of Immune Responsementioning
confidence: 89%
“…The elevation of these cytokine can be linked to the ability of Wip1 to regulate p53 and NF k B pathways. 40,41 These data suggest that Wip1 in immune cells intrinsically controls the sensitivity to DSS-induced colitis through regulation of cytokine production. Yet, the deficiency in Wip1 activity is associated with more severe inflammatory response.…”
Section: Wip1 In Regulation Of Immune Responsementioning
confidence: 89%
“…Only left optic nerve of the rats was crushed as described in previous studies [39, 49] with slight modification. Briefly, after general anesthesia induced by 10 % chloral hydrate, the ON was exposed and isolated after the gently rotated downward in the orbit.…”
Section: Methodsmentioning
confidence: 99%
“…We further demonstrated that Wip1 can modulate neutrophil function to regulate intestinal ischemia/reperfusion injury (26, 37) and inflammatory bowel diseases in a p38 MAPK-dependent manner (25). Moreover, Wip1 can also participate in neuro-inflammation through controlling tumor necrosis factor (TNF)-α synthesis (38) or NF-κB function (39). Further studies identified the interplay between Wip1 and NF-κB which plays an important role in cellular inflammatory response.…”
Section: Wip1 In Inflammationmentioning
confidence: 99%